Myeloablative conditioning in cord blood transplantation for acute myeloid leukemia patients is efficacious only until age 55 - Shinichiro Oshima; Yasuyuki Arai; Tadakazu Kondo; Shingo Yano; Shigeki Hirabayashi; Naoyuki Uchida; Makoto Onizuka; Shigesaburo Miyakoshi; Masatsugu Tanaka; Satoshi Takahashi; Masayuki Hayashi; Toshiro Kawakita; et al. (2025)
Abstract Umbilical cord blood transplantation (CBT) is accepted as an effective treatment for acute myeloid leukemia (AML), and reduced-intensity conditioning (RIC), rather than myeloablative conditioning (MAC) regimens allowed elderly patients to be treated safely. However, appropriate intensities of conditioning regimens are still unclear, especially for middle-aged patients. To compare outcomes after RIC and MAC regimens, we analyzed AML patients aged 16 years or older in the Japanese registry database, who underwent single cord unit CBT between 2010-2019. Median ages of the RIC group ( n = 1353) and the MAC group ( n = 2101) were 59 and 51 years ( P < 0.001), respectively. 5-year overall survival (OS) after MAC was superior to that of RIC (38.3% vs 27.7%, P < 0.001) with lower incidence of relapse (33.9% vs 37.4%, P = 0.029) and better neutrophil engraftment (84.7% vs 75.9%, P < 0.001). Detailed subgroup analysis revealed that age at transplantation is the most important factor affecting 5-year OS in RIC and MAC. This analysis identified a threshold of 55 years, beyond which the superiority of MAC disappeared, irrespective of other factors such as disease status or performance status. In conclusion, RIC may be preferable for patients aged 56 or older in CBT for AML due to higher potential toxicities.